Application of the Accelerated Learning Model to Increase Early Childhood Learning Motivation in Banana Kid's Kindergarten - Narsih; Nita Priyanti; Twi Endah; Mardianingsih; Siti Yasmin; Dewi Sartika (International Conferences on Early Childhood Education Proceedings, 2023)
Early childhood education is very important, because the child's growth and development process is continuous until further development. This development process is determined by various simulations carried out by parents and teachers. In Banana Kid’s Kindergarten, the learning process is carried out through child-centered learning methods that are comfortable and can spark activeness in children so that children have an interest and enthusiasm (motivation) for learning that arises from the children themselves according to their wishes, therefore the purpose of this research was conducted to increase motivation. children's learning through the "Application of the Accelerated Learning Method". The population of this study were children aged 4-6 years at Banana Kid's Kindergarten in Jatisampurna Bekasi District with a qualitative descriptive method approach and technical data collection through observation, interviews, and documentation of learning activities when children feel comfortable choosing their own way of doing activities. The results of implementing the accelerated learning method are very visible and felt by parents and teachers. Today's children always want to come to school and carry out learning activities at school, this is due to their curiosity about the activities they will be doing. Parents also said that now there is no need to work hard to send their children to school because they will immediately get ready for school to get new adventures at school